3D Tracking and Fusion Compositing. - Morse, Brian (linkedin.com, 2017)
Learn how to use 3D tracking data to add 3D objects to a 2D shot in Fusion. Learn how to speed up your workflow by setting up your 3D scene once and using it for all of your shots.